INCLUSIVE BANKING SERVICE TRANSFORMATION STRATEGY TO INCREASE CUSTOMER LOYALTY AT BRI SIDOARJO BRANCH - Fadli Arwan , Dio; Sholichah , Nihayatus; Patria W , Dandy; Devy Pramudiana, Ika (International Journal of Multidisciplinary Reseach, 2025)
This study explores public and financial service dynamics in Sidoarjo Regency through two lenses: flood mitigation in Krian District and inclusive banking at Bank BRI. Both sectors face challenges in transitioning from rigid frameworks to adaptive, human-centric ecosystems. Methodologically, this research employs a qualitative descriptive approach. In the first context, findings indicate that synergy between the Environmental Office (DLH) and Disaster Management Agency (BPBD) is rooted in trust-building and data transparency. However, systemic hurdles like budgetary rigidity and jurisdictional ambiguity regarding central government rivers (BBWS) hinder optimal resource sharing. Parallelly, Bank BRI Sidoarjo enhances customer loyalty through